PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PERSEPSI HARGA TERHADAP PROSES KEPUTUSAN PEMBELIAN KOSMETIK MEREK WARDAH (Studi pada Konsumen Toko Elisha Beauty Kota Semarang) - 14.05.51.0035, Fitri Novita Sari; Sholiha, Euis (Students' Journal of Economic and Management, 2018)
This study aims to test the influence quality product of the process decision purchase, brand image of the process decision purchase and perception price of the process decision purchase of cosmetics brand Wardah at store Elisha Beauty Semarang city. The population in this study is all consumers who buyers product Wardah cosmetics at store Elisha Beauty Semarang city and samples set as much as 100 respondents. Primary data obtained by using the questionnaire closed because of the respondents simply choose the answer is provided. The answer to use the scale likert from the number one up to five. The data is processed using SPSS version of 19.00 program. As a result is all the question valid and all variable is reliable. The result of regressing showed that all variable independent marking positive and significant. According to the test model this third variable independent only able to explain 71,3 percent about process decision purchase. Thus, then quality product have had a positive impact and significant of the process decision the purchase cosmetics brand Wardah., brand image have had a positive impact and significant of the process decision the purchase cosmetics brand Wardah and perception price have had a positive impact and significant of the process decision the purchase cosmetics brand Wardah.Keyword : Quality Product, Brand Image, Perception Price, Process Decision Purchase.